Keterlibatan Jaringan Muslimat NU dalam Memenangkan Khofifah Indar Parawansa di Pemilihan Gubernur Jawa Timur 2018 - Silkania Swarizona; Riaty Raffiudin (LITERATUS, 2021)
In the election for the Governor of East Java in 2018, Khofifah Indar Parawansa finally succeeded in becoming the Governor of East Java after losing in two previous East Java election. Khofifah Indar Parawansa's victory this time could not be separated from the influence of the East Java NU Muslimat network, where Khofifah was the chairman of the NU Muslimat organization. The purpose of this study is to see how the involvement of the Muslimat NU network as a civil society organization and to help Khofifah in winning the East Java election in 2018. This research uses qualitative research methods, with the object of research being Muslimat NU. The results of this study indicate that the NU Muslimat Network can be put to good use by Khofifah Indar Parawansa to make him the Governor of East Java in 2018. This can be seen from two aspects, first is that Khofifah Indar Parawansa has a considerable influence in the Muslimat NU organization. Second, the adherence of NU's Muslimat supporters to Khofifah shows her dominance in the organization. With Khofifah's already strong influence and dominance among Muslimat NU, the Muslimat NU network can implement a resource mobilization strategy to ensure Khofifah Indar Parawansa's victory in the gubernatorial election.